2013
DOI: 10.11130/jei.2013.28.3.375
|View full text |Cite
|
Sign up to set email alerts
|

China-Japan-Korea FTA: A Dual Track Approach to a Trilateral Agreement

Abstract: This paper argues that a China-Japan-Korea Free Trade Agreement (CJK FTA) will have large benefits to the three Northeast Asian countries and significant implications for global multilateral trade. However, several hurdles seem to make an expeditious completion of a CJK FTA, or even bilateral FTAs between Japan and China or between Japan and Korea extremely difficult. Thus, a pragmatic approach would be to follow a dual-track approach in which China and Korea fast-track the completion of a bilateral FTA betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Another key aspect of the CJK relationship is its ongoing Free Trade Agreement (FTA) negotiations, which will provide significant economic and geopolitical benefits to the three Northeast Asian countries as well as fostering new opportunities for global multilateral trade [3]. Since the idea for yearly summits between the three countries was first proposed in 1999, efforts have been made to get a FTA across the line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another key aspect of the CJK relationship is its ongoing Free Trade Agreement (FTA) negotiations, which will provide significant economic and geopolitical benefits to the three Northeast Asian countries as well as fostering new opportunities for global multilateral trade [3]. Since the idea for yearly summits between the three countries was first proposed in 1999, efforts have been made to get a FTA across the line.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an agreement to speed up the negotiations in April 2019, ongoing geopolitical disagreements continue to hinder substantive progress from being made. In addition to the CJK FTA, there are also opportunities for the countries to join the Chinese lead Regional Cooperative Economic Partnership (RCEP) initiative, which has the potential to drive multilateral trade growth in the Asian region [3]. The RCEP trade proposal is at present not in force, with negotiations still very much ongoing, however, a decision by the Trump administration to pull out of the Trans Pacific Partnership (TPP) trade deal, there is now greater optimism that a deal may be struck.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have analyzed economic effects that the trilateral FTA would bring about on trade, gross domestic product (GDP) and industrial structure of each country and the world economy as a whole (Jin, Koo and Sul 2006;Kimura and Ando 2008). Others have examined feasible paths to create a free trade area in Northeast Asia by investigating relative priority between the trilateral FTA and bilateral FTAs among the three countries (Choi 2013;Madhur 2013). Since it took a long time to launch formal negotiations, it was reasonable to undertake the above economics-oriented "prospect" research.…”
Section: Introductionmentioning
confidence: 99%
“…Given the increasingly close ties with China, Korea has put a greater priority on a China-Korea FTA (CKFTA) than the CJKFTA (Yoshimatsu 2015). Korea and Japan had negotiations on a Japan-Korea FTA (JKFTA), but several studies also have shown that a JKFTA would generally be more beneficial to Japan than to Korea (Madhur 2013). The JKFTA negotiation stagnated in 2004 due to both bilateral diplomatic disputes and domestic resistance in both countries from interest groups that would lose out in the free trade agreement (Ahn 2006).…”
Section: Limitations Of Middle Powers and Conditional Bridgingmentioning
confidence: 99%